TO IDENTIFY ORGANIZATIONAL FACTORS LEADING TO CUSTOMER’S INTENTION TO USE ONLINE FOOD DELIVERY SERVICES. (CAHIERS MAGELLANES-NS, 2024)
In an era defined by the rapid digitization of various aspects of our lives, the food delivery industry in India has undergone a transformative shift, with the emergence of online platforms revolutionizing the way consumers access and enjoy their meals. The mid-2000s saw the inception of India's first online food distribution companies, coinciding with the increasing internet penetration and the global proliferation of similar services. The aim of this research is to identify the various organizational factors which impact customer intention to use online food delivery services in the city of Lucknow. The research was underpinned by the Unified Theory of Acceptance and Use of Technology (UTAUT), which is one of the popular theories for investigating the field of online food delivery. Based on a quantitative approach, this research collected data from 310 online food delivery service users. The research found evidence that Zomato and Swiggy held over 80% of the online food delivery service market in the city of Lucknow. The research found evidence for the impact of organizational factors such as delivery staff’s behaviour and perceived security of payment related with food delivery platforms, on customer intention to use online food delivery services. The research contributes by way of identifying the importance of organizational factors in the field of online food delivery services.